2009
DOI: 10.1007/s12640-009-9042-0
|View full text |Cite
|
Sign up to set email alerts
|

The Janus Face of Resveratrol in Astroglial Cells

Abstract: Astroglial cells are key modulators of neuropathology events. Resveratrol, a redox-active compound present in grapes and wine, has a wide range of biological effects. The aim of this study was to investigate whether resveratrol is able to prevent hydrogen peroxide (H(2)O(2))-induced oxidative damage in C6 astroglial cells. We found that following a short oxidative insult (Model I-1 mM H(2)O(2)/30 min), resveratrol increased glutamate uptake (60%), glutamine synthetase (GS) (139%), glutathione (GSH) (120%), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 59 publications
5
42
0
2
Order By: Relevance
“…In our experimental conditions, treatment of astrocytes for 3 days with low concentrations of resveratrol (from 0.1 to 10  μ M) did not induce any change in viability, whereas a toxic effect was observed when the highest concentrations of resveratrol (50 and 100  μ M) were added to cells, characterized by a dose-dependent cell mortality rate higher than 30%. These results are in accordance with those reported by Quincozes-Santos et al [47]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our experimental conditions, treatment of astrocytes for 3 days with low concentrations of resveratrol (from 0.1 to 10  μ M) did not induce any change in viability, whereas a toxic effect was observed when the highest concentrations of resveratrol (50 and 100  μ M) were added to cells, characterized by a dose-dependent cell mortality rate higher than 30%. These results are in accordance with those reported by Quincozes-Santos et al [47]. …”
Section: Discussionsupporting
confidence: 94%
“…Thus, they described a neuroprotective effect for low concentrations of resveratrol when high doses of this polyphenol induced cell toxicity [4446]. Recently, Quincozes-Santos et al [47] evidenced that the nature of the stress could be more important than the resveratrol concentration. They demonstrated that under intense but short oxidative conditions resveratrol was able to protect C6 glioma cells against H 2 O 2 insult while under less intense but lasting oxidative insult, resveratrol had an opposite effect, potentiating the H 2 O 2 -induced damage and resulting in a prooxidant effect.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line was originally derived from rat brain tumors and have oligodendrocytic, astrocytic and neuronal properties (Benda et al, 1968; Parker et al, 1980). C6 cells are widely used as an astrocyte-like cell line (Quincozes-Santos et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Following DCFH-DA exposure, the cells were scraped into phosphate-buffered saline with 0.2 % Triton X-100. The fluorescence was measured in a plate reader (Spectra Max GEMINI XPS, Molecular Devices, USA) with excitation at 485 nm and emission at 520 nm [37]. The results are expressed as percentages relative to the control conditions.…”
Section: Dcfh Oxidationmentioning
confidence: 99%
“…Resveratrol also protects neurons and astrocytes in several neurological disease models, such as epilepsy, stroke, Alzheimer's and Parkinson's diseases [31][32][33][34][35][36]. Our group has shown that resveratrol modulates important glial functions, including glutamate uptake, glutamine synthetase (GS) activity, GSH levels and inflammatory response [22,24,[37][38][39][40]. Recently, we also demonstrated the age-related antioxidant and anti-inflammatory effects of resveratrol in hippocampal astrocytes from adult and aged Wistar rats [29].…”
Section: Introductionmentioning
confidence: 99%